INITIAL DYNAMIC SYSTEM DESIGN FOR OPTIMIZATION OF GRAVITY IRRIGATION WATER MANAGEMENT (OPEN GRAVITATION IRRIGATION) - Hidayat, Asep Kurnia; El Akbar, R. Reza; Kosnayani, Ai Sri (APTIKOM Journal on Computer Science and Information Technologies, 2019)
an expression of conflict in the field. To overcome this problem is a regulation of several parameters,including regulation of planting schedules and reduction of land area. The model of the irrigation water managementsystem used is based on the risk of land failure and the optimum area of land that can be planted. The parameters usedto overcome this problem are planting schedules, risk of land failure and factor k. The k factor is the ratio of wateravailability to water needs. The output of this system is optimal net benefit based on the optimal alternative irrigatedland area. The results of the formula will show the optimal amount of land area that produces optimal net benefitsbased on certain planting schedules and certain effective rainfall. This system will also show that optimization will beachieved if there is a water balance between the availability and needs of irrigation water. The system referred to inthis study is a dynamic system. The purpose of this study is to make a preliminary design of a dynamic system to optimizethe irrigation system of agricultural land. The results obtained in this study were in the form of feedback loops andinteractions between loops with each other in agricultural irrigation systems.